Diagnostic Role of NT Pro BNP in Diabetes Type 2 Patients Associated with Cardiovascular Disease Risk, A Study from Central India (Journal of Medicine, 2010)
Cardiovascular disease is the most frequent cause of death in patient with diabetes. It is difficult to evaluate cardiovascular status of patients with diabetes because of complex symptomatology. NTproBNP, a split peptide from pro BNP molecule is a novel biomarker, released from cardiac myocytes in response to myocardial stretch, cardio vascular disease, endothelial dysfunction and heart failure. We aimed to test that is elevated NTproBNP levels associated with increased risk of cardiovascular disease in diabetes patients in comparison to matched control. Demographic, anthropometric measure, NT pro BNP, lipid profile, blood glucose were estimated and compared among angiographically proven cardiovascular disease patients with diabetes and healthy controls. Univariate and multivariate analysis were carried out to compare individual factor using t-Test, ANOVA and the inter group comparisons were done by using Bon ferroni Post Hoc test. Patients with type 2 diabetes were shown to have higher NTproBNP values (n=50, 1481.021±813.405) than control subjects (n=50, 23.562±23.395) (p